Sympatric and partially synchronic populations of Melitaea phoebe ([Denis & Schiffermüller], 1775) and M. ornata Christoph, 1893 are well known; how common are hybrids? (Lepidoptera: Nymphalidae) - Peter J. C. Russell (SHILAP, 2025)
Locations where Melitaea phoebe ([Denis & Schiffermüller], 1775) and M. ornata Christoph, 1893 are sympatric and at least partially synchronic, across 10 countries, are listed. Comments are made on specimens that are known hybrids and others which have a hybrid appearance, having some characters associated with both species. Albania (nine) and Spain (six) currently record the most locations where both species occur together. Difficulties in species identification of some individual specimens are believed to be the result of hybridisation between these two species.